Prevalence and pattern of utilization of voluntary counseling and testing services and HIV infection in Ogbomoso, southwestern Nigeria - Akhigbe, Roland E. (Medknow Publications & Media Pvt Ltd, 2013)
OBJECTIVE: Human immunodeficiency virus, HIV, infection has been a major problem across the globe with a high socioeconomic burden. Voluntary Counseling and Testing (VCT) is a measure put in place to encourage people to know their HIV status with essential counseling support to help them cope with a positive or a negative test result. This study was carried out to determine the utilization of VCT services, prevalence of HIV among VCT attendees, and the distribution of the viral infection based on gender and age in Ogbomoso, an urban community, southwestern Nigeria. MATERIALS AND METHODS: The health records of patients in Adebayo Alata Primary Health Centre, Ogbomoso South, Nigeria, between 2008 and 2011, were used. RESULTS: A total of 1,490 patients used the VCT services during the period of study, out of which 271 (18.19%) were males and 1,219 (81.81%) were females. A consistent number of people used the VCT service throughout the period of study. HIV infection was higher in females (2.15%) than males (0.54%). The viral infection was more prevalent in people above 14 years of age (2.62%). However, none of these differences observed in gender and age were statistically significant (P < 0.05). CONCLUSION: It was concluded that HIV infection has neither gender nor age bias. Efforts should be made to increase the provision of VCT services and ensure its continued utilization in an attempt to maintain a healthy social and reproductive health culture, improve maternal and child health in the context of HIV transmission, and improve global child survival.